Testing a putative species-independent translation enhancer: "3 Hairpin" motif - Zhang, Ting (My University, 2010)
Cell-free (CF) protein synthesis enables rapid production and engineering of recombinant proteins. Existing CF systems differ substantially from each other with respect to efficiency and scalability. We examined the possibility and mechanism of recently reported "Three Hairpin" (3HP) motif included in mRNA to enhance translation using a high-efficiency wheat germ (WG) CF extract. In this work, enhanced GFO expression plasmids constructed with and without 3HP were transcribed and translated. The differences in levels of transcription and translation from the 3HP and control constructs were detected by DNA and GFP fluorescence, respectively. Although 3HP reportedly gave universal ~10-fold enhancement of cell-free translation, we observed no comparable increases in either mRNA or protein yield associated with 3HP. We tentatively assign this result to the higher efficiency of the WG CF translation system used in our laboratory compared to the coupled-CF protein production system described previously.
21 p.
Keywords: Biohemistry